2011
DOI: 10.1080/07373937.2010.513780
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Spray-Dryer Air Temperatures on Encapsulated Mandarin Oil

Abstract: The influence of inlet and exit air temperatures (160-200 and 80-100 C, respectively) on the spray drying of mandarin oil was evaluated by using a three-level factor design. For optimization, dryer evaporative rate, volatile oil retention, and microencapsulation efficiency were considered as response variables. The response surface analysis produced significant (p < 0.05) polynomial regression equations that were successfully fitted for all response variables and no significant (p > 0.05) lack of fit was indic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
31
0
1

Year Published

2013
2013
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 65 publications
(39 citation statements)
references
References 24 publications
(26 reference statements)
5
31
0
1
Order By: Relevance
“…The efficiency of inner oil retention ranged from 96.8% to 98.8% for all wall materials evaluated. These values are similar to those reported for microencapsulated lime essential oil with gum Arabic and maltodextrin (99%) (BRINGAS-LANTIGUA; VALDÉS; PINO, 2012), and mandarin microencapsulated essential oil (KIM; MORR, 1996), and are highly related to microencapsulated orange essential oil (BRINGAS-LANTIGUA et al, 2011), which range between 72.7%, 85.7% and 82-100% for microencapsulated limonene (SOOTTITANTAWAT et al, 2005; MURÚA-PAGOLA; BERISTAIN-GUEVARA; MARTINEZ-BUSTOS, 2009). Boutboul et al (2002) reported that the aroma retention was increased with the specific area of starch materials.…”
Section: Retention Of Orange Peel Oil During Spray Dryingsupporting
confidence: 73%
See 1 more Smart Citation
“…The efficiency of inner oil retention ranged from 96.8% to 98.8% for all wall materials evaluated. These values are similar to those reported for microencapsulated lime essential oil with gum Arabic and maltodextrin (99%) (BRINGAS-LANTIGUA; VALDÉS; PINO, 2012), and mandarin microencapsulated essential oil (KIM; MORR, 1996), and are highly related to microencapsulated orange essential oil (BRINGAS-LANTIGUA et al, 2011), which range between 72.7%, 85.7% and 82-100% for microencapsulated limonene (SOOTTITANTAWAT et al, 2005; MURÚA-PAGOLA; BERISTAIN-GUEVARA; MARTINEZ-BUSTOS, 2009). Boutboul et al (2002) reported that the aroma retention was increased with the specific area of starch materials.…”
Section: Retention Of Orange Peel Oil During Spray Dryingsupporting
confidence: 73%
“…Huynh et al (2008) reported that encapsulation of lemon myrtle oil, in which the outlet air temperature of the spray dryer had little effect on oil retention, surface oil significantly increased with increasing outlet air temperature. However, Bringas-Lantigua et al (2011) reported that an inlet air temperature of 220 °C and an outlet air temperature of 85 °C were optimal for the spray drying of lime essential oil. Drusch and Schwarz (2006) reported that moderate spraydrying conditions (air inlet temperature of 160 °C and outlet air temperature of 60 °C) were advantageous since ballooning of particles and lipid oxidation during spray drying were limited compared to drying at high spray-drying temperatures.…”
Section: External Morphology Of the Microcapsulesmentioning
confidence: 99%
“…0.02À1000 Baranauskiené et al, 2007;Bhandari et al, 1992Bhandari et al, , 1999Bringas-Lantigua et al, 2011;Cadwallader et al, 2010;Charve and Reineccius, 2009;Fabra et al, 2012;Kaasgaard and Keller, 2010;Li et al, 2013;Ma et al, 2013;Paramita et al, 2012;Penbunditkul et al, 2012;Ramoneda et al, 2011;Rodríguez et al, 2013;Shah et al, 2012;Sillick and Gregson, 2012;Soottitantawat et al, 2005;Yuliani et al, 2006a,b. Flavor stability: flavor release GC, DVS fast GC-FID, melting enthalpy, e-nose, liquid-gas chromatography Essential information for the stability and shelf-life of encapsulates.…”
Section: Hplcmentioning
confidence: 97%
“…Baranauskiené et al, 2006Baranauskiené et al, , 2007Bringas-Lantigua et al, 2011;Chen et al, 2013;Goula and Adamopoulos, 2012;Paramita et al, 2012;Fabra et al, 2012;Kalogeropoulos et al, 2010;Ko et al, 2012;Li et al, 2013;Ma et al, 2013;Marcuzzo et al, 2010;McNamee et al, 1998McNamee et al, , 2001Penbunditkul et al, 2012;Shah et al, 2012. Multiple pathways, not easy to identify the best one for each encapsulate.…”
Section: Glass Transition and Moisture Sorptionmentioning
confidence: 97%
See 1 more Smart Citation